Friend or Foe? Exploring the Factors that Determine the Difference Between Positive and Negative Effects on Photosynthesis in Response to Insect Herbivory - Frier, John Paul Délano; Hernández, Carla Vanessa Sánchez; Tiessen, Axel (IntechOpen, 2012)
None